Evaluación de Dos Niveles de Energía Digestible en base a los Estándares Nutricionales del NRC (1995) en Dietas de Crecimiento para Cuyes (Cavia porcellus L) - Airahuacho Bautista, Felix Esteban (2017)
The aim of this research was to assess levels of 2.7 and 2.9 Mcal of digestible energy (ED/kg of feed) and amino acids densities (DA) of 100, 110 and 120% in relation to nutritional standards of the NRC (1995) on productive performance of genotype improved guinea pigs after weaning (2-6 weeks of age). Diets were formulated considering the amino acids concentration relative to the level of ED (g/Mcal) with inclusion of vitamin Cin the pelleted feed because no fresh forage was used. A randomized complete design for all treatments and a factorial arrangement 2x3 were used, having as factors two levels of ED (2.7 and 2.9 Mcal/kg) and three DA (100, 110 and 120%), and without considering the control treatment. Covariance analysis was performed, considering the initial weight as a covariate, and Bonferroni adjustment to determine the difference between treatments and factors. The more efficient treatments for feed conversion were 3.0 Mcal ED/kg (control) and 2.9 Mcal ED/kg, 120% DA (3.38 and 3.32, respectively), while treatment 2.7 Mcal ED/kg, 100% DA was the less efficient (3.82). Data analysis in the factorial arrangement showed that the 2.9 Mcal ED/kg factor improved weight gain, feed intake, feed conversion and carcass yield and without differences by the effect of the DA factor. The weight of viscera (liver, kidney, and heart) showed no statistical difference.